2008
DOI: 10.1208/s12249-008-9111-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Venlafaxine Hydrochloride for Transdermal Delivery: Passive Diffusion and Iontophoresis

Abstract: Abstract. The objective of the study was to investigate in vitro transdermal delivery of venlafaxine hydrochloride across the pigskin by passive diffusion and iontophoresis. For passive diffusion, experiments were carried out in Franz diffusion cell whereas for iontophoretic permeation, the diffusion cell was modified to contain both the donor and return electrode on the same side of skin. Anodal iontophoresis was carried out using a current density of 0.5 mA/cm 2 . Donor concentrations used were 585.5 mg/ml (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Nanoparticles have been shown to be delivered to specific sites by size-dependant passive targeting [13] , [14] . Passive delivery occurs when nanoparticles are transported through leaky tumor capillary fenestrations into the tumor cells by diffusion or convection [15] . Active targeting involves the coupling the target-specific molecules, such as ligands, binding sites, or antibodies, to the surface of the nanoparticles to assist drug distribution to specific target tissues [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have been shown to be delivered to specific sites by size-dependant passive targeting [13] , [14] . Passive delivery occurs when nanoparticles are transported through leaky tumor capillary fenestrations into the tumor cells by diffusion or convection [15] . Active targeting involves the coupling the target-specific molecules, such as ligands, binding sites, or antibodies, to the surface of the nanoparticles to assist drug distribution to specific target tissues [16] .…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by a higher affinity between the positively charged drug and this negatively charged nanoparticles (zeta potential −55 mv). pKa value of venlafaxine HCl was found to be 9.6, which indicated that the drug was completely ionized at pH 7.4 ( Singh et al 2008 ). The release rate was not different between the prepared formulae.…”
Section: Resultsmentioning
confidence: 99%
“…During the Table 1. Chemical structure and pKa of the selected seven drugs [21][22][23][24][25][26][27] wileyonlinelibrary.com/jctb course of the experiments, samples were collected at predefined time points and quenched by the addition of 1 mL ascorbic acid solution (10 mmol L -1 ). Samples were filtered through 0.45 μm nylon filers for NDMA analysis.…”
Section: Chlorination Experiments Proceduresmentioning
confidence: 99%
“…In the present study, seven widely used psychoactive drugs were selected containing a DMA functional group and detected in wastewater at concentrations from ng L −1 to µg L −1 . Their names and chemical structures are summarized in Table . The NDMA formation potentials of these psychoactive drugs were assessed during free chlorine (NaOCl) and chlorine dioxide (ClO 2 ) disinfection processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation